Synthesis and characterization of ZnO-reinforced with graphene nanolayer nanocomposites: electrical conductivity and optical band gap analysis - Guler, Omer; Guler, Seval Hale; Basgoz, Oykum; Albayrak, Muhammet Gokhan; Yahia, I. S. (Iop Publishing Ltd, 2019)
In this study, the effect of liquid phase exfoliation method on the electrical and optical properties of sol-gel ZnO coated with graphene nanolayers was investigated. The graphene nanolayers were produced by liquid phase exfoliation method and it was used as reinforcements. Two types of ZnO matrix were used as matrix. In a group of samples, ZnO was produced nano-sized by sol-gel method and graphene nanolayers were added. In the other group of samples, ZnO was commercially supplied and graphene nanostructures were added for comparison. The electrical and optical properties of the resulting nanocomposites were investigated. The electrical conductivity values of the sol-gel-produced ZnO matrix composition was compared the commercially available ZnO matrix nanocomposites. The electrical conductivity of samples having commercial ZnO matrix are higher than samples having sol-gel ZnO matrix. However, temperature dependence of electrical conductivity was greater in sol-gel-produced ZnO matrix composites. In optical properties, it is seen that the composites using the sol-gel-produced ZnO exhibit better properties. The E-g value of commercial ZnO matrix having 1 wt% graphene is 3.19 eV while the E-g value of the sol-gel-produced ZnO matrix containing graphene is 3.16 eV. The studied nanocomposites of ZnO coated with graphene nanolayers can be used in variety of applications such as environmental, biomedical, catalytic/photocatalytic activity.
Keywords: graphene/ZnO nanocomposites; liquid phase exfoliation; sol-gel; electrical conductivity; optical bandgap